The Impact of Active Herpes Simplex Virus Infection on Human Immunodeficiency Virus Load - Mole, Larry; Ripich, Stefan; Margolis, Dan; Holodniy, Mark (The Journal of infectious diseases, 1997)
The effect of a concurrent herpes simplex virus (HSV) infection on human immunodeficiency virus type 1 (HIV-1) load was evaluated. Sixteen subjects were identified with an active HSV infection and had pre-outbreak, acute-phase, and post-outbreak plasma (n = 16) and peripheral blood mononuclear cell (PBMC) (n = 8) samples for evaluation. All subjects were treated for an acute HSV outbreak with acyclovir for 10 days, followed by chronic prophylaxis. HIV-1 plasma RNA levels were determined by branched DNA, and intracellular HIV gag mRNA copy numbers were determined by quantitative reverse transcriptase-polymerase chain reaction ELISA. Plasma virus load increased a median of 3.4-fold during the acute outbreak (range, 0- to 10-fold; P = .002), while post-outbreak levels (30–45 days after the appearance of lesions) remained above pre-outbreak, baseline levels in some subjects. Intracellular HIV gag mRNA increased during the outbreak as well. Thus, an acute HSV episode can result in increased HIV transcription and plasma virus load.